Football Shooting: Using Plyometric Drills - Zaenal, Zaenal; Indrayogi, Indrayogi; Fauzi, Riza Sukma (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
The purpose of this study is to ascertain how football shooting performance among extracurricular students at State Senior High School 1 Lohbener, Indramayu Regency, is affected by plyometric exercise. This study employs an experimental methodology and a "One Group Pretest Posttest Design" test design. 47 extracurricular students from State Senior High School 1 Lohbener Indramayu, Indramayu Regency, who were selected using a purposive selection technique made up the population of this study. The players are extracurricular students at State Senior High School 1 Lohbener, Indramayu Regency who are still actively engaged in training, and the criteria for selecting this sample include an attendance list of at least 75% of training (actively participating in training throughout treatment). There were sixteen people who met these requirements. The vertical leap test and a shooting skill test were used to measure the leg power of the participants. The t test was utilized in data analysis with a 5% level of significance. With tcount 2.390 > ttable 2.131, a significance value of 0.030 0.05, and an increase in leg power of 2.24%, the findings indicated that plyometric training significantly increased leg power in extracurricular students at State Senior High School 1 Lohbener Indramayu Regency. With a tcount of 3.738 > ttable of 2.131, a significance value of 0.002 0.05, and a percentage rise of 5.50%, plyometric training had a significant impact on the growth in shooting for extracurricular students at State Senior High School 1 Lohbener Indramayu Regency